Epistemologi Penafsiran Ilmiah al-Qur’an - Sujiat Zubaidi Saleh (TSAQAFAH, 2011)
The main objective in interpretating al-Qur’an is to explain the will of God and the operationalization of the will in the field of faith, laws, or ethics. At the phase of Islamic civilization, when the linguistic and philosophy science codified, raises the various method (manhaj), and interpretation streams (ittijahat), exegesis school (madzhab) of al-Qur’an. In addition, also found in various shades of interpretation such as: fiqhi, kalami, balaghi, and isyari/ sufi, even philosophical. It was also discovered methods of tafsir ‘ilmi oriented to the utilization of the discovering science in order to prove the truth of scientific fact. The last pattern was ignited pro and contra among scholars and mufassir. As we know that alQur’an was not descended in the condition of cultural vacuum but it is a form of dialectics and the response to the condition and social situation, politic, and religion. This is relevant to the characteristics of al-Qur’an which can be applied throughout the periods. As we understood that interpretation is one of reflections of thought and civilization products. It always developed and influenced by the dynamics of human civilization, so in its development, science and al-Qur’an can be brought together in dialogue, although with some prerequisites specified interpretation.